THE USE OF LANGUAGE OF NEGOTIATION BETWEEN SELLERS AND BUYERS AT KARISA TRADITIONAL MARKET JENEPONTO REGENCY - Nur Fadillah; Abdul Wahid; Andi Hajar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This study analyzed the use of language of negotiation between sellers and buyers at Karisa traditional market in Jeneponto Regency using a qualitative approach. Data was collected through observation, recording, and interviews, and analyzed using discourse analysis. The study found that both sellers and buyers use various linguistic strategies, including bargaining, flattery, and persuasive language, to achieve a successful negotiation outcome. Additionally, the use of local languages, such as Bugis, Makassar, and Jeneponto, is common in the negotiation process to establish a sense of familiarity and trust. The study suggests that the use of local languages should be considered in the negotiation process, particularly in traditional markets. Based on these results, The study did not identify a single